2003
DOI: 10.1111/j.1151-2916.2003.tb03406.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and High‐Temperature Mechanical Behavior of an Oxide/Oxide Composite

Abstract: An oxide/oxide ceramic fiber‐matrix composite (CMC) has been extensively characterized for high‐temperature aerospace structural applications. This CMC is called GEN‐IV™, and it has a porous and cracked aluminosilicate matrix reinforced by 3M Nextel 610™ alumina fibers woven in a balanced eight harness weave (8HSW). This CMC has been specifically designed without an interphase between the fiber and matrix, and it relies on the porous matrix for flaw tolerance. Stress‐strain response is nearly linear to failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 47 publications
6
50
0
Order By: Relevance
“…After the UTS is reached, appreciable inelastic strains develop at near constant stress. These observations are consistent with the results reported for the porousmatrix ceramic composites in the ±45°orientation [24,25]. The elastic modulus (46 GPa) and UTS (55 MPa) obtained for the ±45°orientation are considerably lower than the corresponding values for the 0°/90°specimens.…”
Section: Monotonic Tensionsupporting
confidence: 94%
“…After the UTS is reached, appreciable inelastic strains develop at near constant stress. These observations are consistent with the results reported for the porousmatrix ceramic composites in the ±45°orientation [24,25]. The elastic modulus (46 GPa) and UTS (55 MPa) obtained for the ±45°orientation are considerably lower than the corresponding values for the 0°/90°specimens.…”
Section: Monotonic Tensionsupporting
confidence: 94%
“…For these materials, fatigue is significantly more damaging than creep. Conversely, for porous-matrix oxide-oxide CMCs, creep is considerably more damaging than fatigue [28,29]. In addition, the prior studies [29,30] revealed that creep performance of the porous-matrix Nextel™720/alumina (N720/A) oxide-oxide composite deteriorates drastically in the presence of steam.…”
Section: Introductionmentioning
confidence: 96%
“…Oxide–oxide CMCs exhibit damage tolerance combined with inherent oxidation resistance, and have good high‐temperature mechanical properties in air . However, recent studies show dramatic degradation of mechanical performance of oxide–oxide CMCs at elevated temperature in steam .…”
Section: Introductionmentioning
confidence: 99%